Krebs von den Lungen-6 (KL-6) in cerebrospinal fluid from neurosarcoidosis patients - Bocci, Silvia; D'Alessandro, Miriana; Bergantini, Laura; Cerase, Alfonso; Ulivelli, Monica; Rottoli, Paola; Cavallaro, Dalila; Gangi, Sara; Bargagli, Elena; Giannini, Fabio (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2023)
Background: Krebs von den Lungen-6 (KL-6) is a high molecular weight (MW) glycoprotein mainly secreted by type II pneumocytes because of lung damage or during regeneration. Neurosarcoidosis (NS), where sarcoid granulomas involve the nervous system, occurs in 5-20% of patients with sarcoidosis. No data is currently available on KL-6 in serum or CSF of NS patients. The present study compared KL-6 concentrations in serum and CSF of NS patients versus others with neurodegenerative (ND) or chronic inflammatory demyelinating (DM) diseases. Materials and methods: Nine NS patients (mean age 46.2 years, range 16-61 years, M/F 5/4), nine patients with a chronic neurodegenerative disease (mean age 53.1 years, range 37-65 years, M/F 5/4) and nine patients with a chronic demyelinating disease (mean age 46.3 years, range 18-65 years, M/F 5/4) were retrospectively enrolled. Results: Measurable CSF concentrations of KL-6 were detected in 7/9 NS patients but in no ND or DM patients. No significant differences in CSF concentrations of ACE were observed between the three groups (p=0.0819). In NS patients, CSF concentrations of KL-6 were directly correlated with CSF albumin index (r=0.98; p<0.0001), albumin (r=0.979, p=0.0001), IgG (r=0.928, p=0.0009) and total protein concentrations (r=0.945, p=0.0004). Discussion: KL-6 is a high MW protein, under physiological conditions it is unlikely to cross the blood-brain barrier. We found KL-6 in CSF from NS and not from ND and DM patients. The finding sustains the specificity of changes in KL-6 in this granulomatous disease, suggesting it as a candidate biomarker for recognition of NS.